Reconstruction of the Nasal Ala using the Nasolabial Flap - ملحم, فراس (Latakia University Journal -Medical Sciences Series, 2021)
Nose is considered to be the most complex structure on the face, considering its three-dimensional topography and its concave and convex contour. Nasal reconstruction has a history as old as plastic surgery. Nasolabial flaps are one of the most preferred methods for nasal reconstruction. Each part of the nose has features that need special attention while performing reconstruction. The nasal ala is a complex structure whose inherent convexity and skin characteristics make reconstruction of the area a challenge. The unique fibrofatty soft tissues of the alar lobules provide support to this three-dimensional structure with negligible underlying native cartiage. This study aims to evaluate the reconstruction of the nasal ala using the nasolabial flap. Nasolbial skin is subdermally dissected and turned over into the defect to create both the inner and outer lining of the ala. The proximity of the nasolabial region, having a robust blood supply and very good donor scar are the key advantages of nasolabial flaps. With proper technique, the nasolabial flap can provide excellent and repeatable results when reconstruction a defect on nasal ala. A retrospective study of our outcome of 10 performed nasal alar reconstruction. All these patients were operated using the proposed surgical technique between 2018 and 2020 in Tishreen University Hospital in Lattakia, Syria. Patients ranged from 50 to 70 years (mean 60 years). Seven patients were males. The reconstruction was performed ranging from 5 to 13 days after the tumur initial exision. Results of surgery were graded as excellent to good depending upon the outcome of the flap. Minor complications were noted but none required a separate operative procedure. We have found this procedure to be reliable, technically easy, and esthetically acceptable.